Electronic government and the information systems perspective : 6th International Conference, EGOVIS 2017, Lyon, France, August 28-31, 2017, Proceedings - Kő, Andrea ; Francesconi, Enrico (Springer, 2020)
This book constitutes the refereed proceedings of the 6th International Conference on Electronic Government and the Information Systems Perspective, EGOVIS 2017, held in Lyon, France, in August 2017. The 20 revised full papers presented were carefully reviewed and selected from 24 submissions. The papers areorganized in the following topical sections: digitalization and transparency; open data ecosystems; intelligent systems in e-government; e-government research and intelligent systems; m-government and inclusion; e-government cases - data knowledge management; and knowledge management in the context of e-government.Digitalization as Challenge for Electronic Government / Roland Traunmüller -- Tyrant Leaders as e-Government Service Promoters : The Role of Transparency and Tyranny in the Implementation of e-Government Service / Yuting Lin, Andreas Eisingerich, Hersen Doong -- Electronic Forms-Based Model of Public Administration Operations / Péter József Kiss, Gábor Klimkó -- E-Government, e-Governance and Urban Planning : Towards a Complete Digital Planning Process / Beatriz Santos -- Open Data Ecosystems/ Sébastien Martin, Slim Turki, Samuel Renault -- Enabling Spatial Queries in Open Government Data Portals / Pedro Arthur de Fernandes Vasconcelos, Wensttay de Sousa Alencar, Victor Hugo da Silva Ribeiro, Natarajan Ferreira Rodrigues, Fabio de Gomes Andrade -- Practical Use Cases for Linked Open Data in eGovernment Demonstrated on the Czech Republic / Martin Nečaský, Jakub Klímek, Petr Škoda -- Ontological Models of Legal Contents and Users' Activities for EU e-Participation Services / P. Schmitz, E. Francesconi, B. Batouche, S.P. Landercy, V. Touly -- Complexity Based Analysis of eGov Ontologies / Jean Vincent Fonou-Dombeu, Yannick Kazela Kazadi -- Process-Based Query Tool to Rationalize Document Bases / Katalin Ternai, Ildikó Szabó -- Proposal for Application of Data Science Methods in E-Government / Bálint Molnár -- A System Architecture for a Transnational Data Infrastructure Supporting Maritime Spatial Planning / Henning Sten Hansen, Ida Maria Reiter, Lise Schrøder -- Exploring Usability and Acceptance Factors of m-Government Systems for Elderly / Tamás Molnár, Andrea Kő, Bálint Mátyus -- Designing Human Behavior Through Social Influence in Mobile Crowdsourcing with Micro-communities / Mizuki Sakamoto, Kota Gushima, Todorka Alexandrova, Tatsuo Nakajima -- Institutionalization of the Reengineering of Strategic Management Processes in the Brazilian Public Management : A Case Study in Federal Government Organizations / Marçal Chagas, Ricardo Gomes, Paulo Henrique Bermejo, José Martins -- The Potential of the Estonian e-Governance Infrastructure in Supporting Displaced Estonian Residents / Lőrinc Thurnay, Benjamin Klasche, Katrin Nyman-Metcalf, Ingrid Pappel, Dirk Draheim -- The Challenge of Accelerating Greek Judicial Procedure / Demetrios Sarantis -- Social Network for Education : What Are the Resources Desired by Students? / Guilherme Henrique Alves Borges, Paulo Henrique de Souza Bermejo, Everton Leonardo de Almeida, Thiago Almeida Martins Marques -- Driving Forces and Design of the TTÜ e-Governance Technologies and Services Master's Program / Ingrid Pappel, Karin Oolu, Ingmar Pappel, Dirk Draheim -- Strategic Planning in the Public Sector : How Can Brazilian Public Universities Transform Their Management, Computerise Processes and Improve Monitoring? / Lucas Cezar Mendonça, Fábio Henrique dos Anjos, Paulo Henrique de Souza Bermejo, Tomás Dias Sant'Ana, Guilherme Henrique Alves Borges.